A Cross Sectional Discriptive Study of Analysis of Lambdoid And Squamous Sutures Closure by Ct Scan for Age Estimation - Kalpesh M Zanzrukiya1 , Lavlesh Kumar2, Ashish A Bhalodiya3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background– Identification is fixation of an individuality by various physical and biological parameters.An individual’s age determination is very important in various civil and criminal medicolegal cases. Ageestimation by cranial sutures closure is an old method. This study was conducted to analyze closure oflambdoid and squamous sutures for age estimation in living individuals by CT scan.Objectives– To study the pattern of closure of lambdoid and squamous sutures with relation to age ofperson. To detect bilateral and bisexual variations in same.Materials & Methods–We had done a descriptive cross-sectional study by CT scan head of 130 living adultpersons and analyzed them for closure status of lambdoid and squamous sutures in co-relation to age.Results– In Lambdoid suture complete closure observed 5yrs earlier in upper 2/3rd(L1&L2) parts of rightside than left side in both sex while while complete closure observed very late ages(>75yrs) or not atall(lapsed union) in lower 1/3rd(L3) part. Both sides of Squamous sutures follow more or less same patternfor closure in relation to age and sex while complete closure observed at very late ages(>75yrs) or not atall(lapsed union).Conclusion– Closure of Lambdoid and Squamous sutures should be used only as corroborative to othercriteria and evidences for age estimation as they might be unreliable as standalone until proven otherwise.